Bercocok Tanam dalam Perspektif Hadis: Analisis Tekstual dan Kontekstual - Ali, Muhammad (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
Farming is a typical way for human beings in order to provide food for survival in life and is frequently done in an area close to their settlement. To guarantee the availability of food for daily life, human beings farm a variety of plants not olny for their own needs, but also for generations to come. This writing is aimed at assessing and analyzing a farming-related hadith on both its sanad and matan. From sanad and matan perspective, the hadith is sound (sahih). Analyzing the hadith text and context, it is found that many lessons may be learnt, particularly the emphasis of the hadith on human effort to do farming in all seasons and occasions, since the harvest may be beneficial for them or for the others. The long term benefits of the farming is to ensure that the earth is and will always be a fertile ground for human beings to live, and to ensure the availability of food for all. From Islamic perspective, the benefits for others may act as the farmers’ wordly philantrophic actions, and may lead to heavenly endless regards